Development of vibration-assisted micro-milling device and effect of vibration parameters on surface quality and exit-burr. (May 2019) - Li, Guo; Wang, Bo; Xue, Jiadai; Qu, Da; Zhang, Peng
Vibration-assisted cutting is an important technology with better performance in manufacturing micro-scaled components, compared with conventional cutting technology. This article first illustrates the development of vibration-assisted micro-milling device which is made based on piezoelectric plates and shows different vibration types with vibration principle of this device. It is then tested stable to output vibration with a frequency accuracy of 100 Hz and an amplitude accuracy of 100 nm. Two groups of experiments in micro-milling 6061 aluminum alloy are carried out. Compared with conventional micro-milling, using vibration assist is verified more effective in improving surface integrity and quality. Furthermore, with a proposed method of characterizing exit-burr size, the influences of vibration frequency and amplitude on surface roughness and exit-burr size are discussed. As a result, the mean surface roughness is found positive related to vibration frequency and negative related to vibration amplitude in most of the study range. To make guidance on optimizing vibration machining parameters, cubic polynomial fitting with 95% prediction interval is of enough accuracy.